The myth of the shrinking state globalization and the state in India - Nayar, Baldev Raj. (New Delhi ; Oxford : Oxford University Press, 2009)
This study investigates the nature of the impact of globalization on the Indian state. It takes as its point of departure the thesis that globalization has resulted in the erosion of the economic and welfare roles of the state. The author argues in favour of the continued expansion of these roles.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Globalization -- Political aspects -- India; Globalization -- Social aspects -- India; India -- Social policy; India -- Economic policy; India -- Politics and government